2017
DOI: 10.5617/jeb.4560
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral vein detection using electrical impedance method

Abstract: The electrical impedance method of peripheral vein detection is a novel approach, which offers the advantages of not being expensive and the capability of minimizing and reducing the difficulty of achieving intravenous access in many patients, especially pediatric and obese patients. The electrical impedance method of peripheral vein detection is based on the measurement of electrical impedance using the 4-electrode technique by applying a known alternating current of frequency 100 kHz and constant amplitude t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…It should be noted that the correlation between the contrast and depth or between the contrast and diameter of veins is only a rough guide. The behaviour of variance occurs when the matter is related to one of the two variables (depth or diameter) with the stability of the other variable, where it can be traced by drawing a contrast scheme with one of the transformers by fixing the value of the other variable [32]. Figure 8 depicts a contrast scheme with depth.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the correlation between the contrast and depth or between the contrast and diameter of veins is only a rough guide. The behaviour of variance occurs when the matter is related to one of the two variables (depth or diameter) with the stability of the other variable, where it can be traced by drawing a contrast scheme with one of the transformers by fixing the value of the other variable [32]. Figure 8 depicts a contrast scheme with depth.…”
Section: Resultsmentioning
confidence: 99%
“…Although the nature of other soft tissue tumors cannot be clarified by ultrasound, the appearance, internal echo structure, peripheral boundary conditions, blood flow conditions, and whether there is infiltration into surrounding structures can be preliminarily treated by ultrasound for benign and malignant tumors. Relevant scholars summarized 53 cases of soft tissue masses in other parts of the maxillofacial area except for maxillofacial area using CDFI technology [ 10 ]. All the bleeding flow velocity and resistance index were measured, and they found that there was a significant difference in the maximum blood flow velocity around benign and malignant tumors.…”
Section: Related Workmentioning
confidence: 99%
“…Figure 1 shows the electrical resistivity of biological tissues in the study area in different frequencies including 100 kHz [11]. Four electrode system configuration was proposed in this study to provide the desired accuracy for bio-impedance measurement, thus two outer electrodes are used to inject a small alternating current into the human body the voltage drop is measured to calculate the complex impedance [12].…”
Section: Introductionmentioning
confidence: 99%